Development of Course Booking System (Front-end & Back-end) Based on Mobile Application to Help Tutoring Elementary and Junior High School in Indonesia - Febrianti, Elsa (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2022)
Tutoring is informal education to help students who have problems outside of school. Students are helped to adjust to their learning situation so that they can develop efficiently according to their abilities. In Indonesia, there are still many students who do not understand the learning material delivered at school, so they must deepen the material outside of school learning. Especially since the COVID-19 pandemic hit, the effectiveness of learning activities has decreased because the learning process is carried out online which results in less interactive learning. Therefore, the EduAlecta application was created which is engaged in digital-based education. The EduAlecta app can help teachers increase their income and connect with students who need tutoring outside of school hours. The EduAlecta application system has the advantage of applying GPS so that students can determine the study location they want and students can arrange the tutoring they ordered. The method used in the front-end design is user centered design and the back-end design method uses waterfall.